Making mobile financial services stick: an empirical investigation into user attitudes and intentions for sustainable adoption - Labaran Isiaku; Abubakar Sadiq Muhammad; Dokun Oluwajana; Adacha Kwala (Journal of Innovative Digital Transformation)
Purpose – This study examined the factors that affect attitudes and intentions for sustainable adoption of mobile financial services (MFS) in Nigeria. Design/methodology/approach – The study expands the Technology Acceptance Model (TAM) by incorporating constructs like perceived service quality, perceived ease of use, perceived usefulness, perceived credibility, perceived trust and attitude. It includes an empirical analysis with 382 participants and qualitative insights from semi-structured interviews to investigate the challenges and opportunities associated with MFS adoption in Nigeria. Findings – The findings show that perceived service quality, perceived usefulness and attitude positively influence the adoption of MFS. However, perceived ease of use and perceived credibility have little impact on adoption. Qualitative insights from Study 2 shed light on the challenges and opportunities as well as the reasons behind the insignificant effects of perceived ease of use and perceived credibility. Originality/value – This research stands out by using a mixed-methods approach, blending quantitative and qualitative analysis to provide a more detailed understanding of the factors influencing MFS adoption.